2014
DOI: 10.1038/ejcn.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataracts following total parenteral nutrition (TPN) use during pregnancy

Abstract: We describe a case of congenital cataracts in a newborn whose mother received total parenteral nutrition (TPN) throughout her pregnancy. We discuss the potential mechanisms by which TPN may have been causally linked to cataract formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Only 2 neonates were born prematurely, with 1 suffering from minor facial deformities and acute respiratory distress syndrome 10 . Still, various adverse fetal outcomes most likely linked to micronutrient deficiencies have been reported 12 , 15 , 20 . Specifically, deficiencies in fat‐soluble vitamins have resulted in congenital anomalies, as seen in several patients with intestinal malabsorption 15 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 neonates were born prematurely, with 1 suffering from minor facial deformities and acute respiratory distress syndrome 10 . Still, various adverse fetal outcomes most likely linked to micronutrient deficiencies have been reported 12 , 15 , 20 . Specifically, deficiencies in fat‐soluble vitamins have resulted in congenital anomalies, as seen in several patients with intestinal malabsorption 15 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic literature review, we identified 14 publications describing 15 cases of parenteral nutrition from preconception to delivery in 14 women dependent on long‐term HPN 7 20 . Here, we additionally report the case of a 26‐year‐old Caucasian woman with SBS secondary to recurrent thromboembolic mesenteric infarctions receiving both HPN and high‐dose dual anticoagulation throughout pregnancy and beyond.…”
mentioning
confidence: 99%